2019
DOI: 10.1248/bpb.b19-00156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Expression Time of Ganciclovir-Induced Adverse Events Using JADER and FAERS

Abstract: Investigation of the occurrence time of adverse drug reactions helps to prevent the development and aggravation of adverse reactions, but the expression time of ganciclovir-induced adverse events has not been elucidated. In this study, using databases of spontaneous adverse event reports, the Japanese Adverse Drug Event Report database (JADER) and the U.S. Food and Drug Administration (FDA)'s Adverse Event Reporting System (FAERS), the incidence of adverse reactions due to ganciclovir and their expression time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…However, with inhibition and control on the virus in children via small-dose ganciclovir, their liver function slowly recovers. It has been previously reported that ganciclovir may affect the liver and kidney function of patients (23). We suspected that small-dose ganciclovir would exert less effect on the liver, making it more effective in improving the liver function.…”
Section: Discussionmentioning
confidence: 92%
“…However, with inhibition and control on the virus in children via small-dose ganciclovir, their liver function slowly recovers. It has been previously reported that ganciclovir may affect the liver and kidney function of patients (23). We suspected that small-dose ganciclovir would exert less effect on the liver, making it more effective in improving the liver function.…”
Section: Discussionmentioning
confidence: 92%
“…16 In principle, the onset time was calculated as "(onset date of adverse event) -(administration start date) +0.5". 17 The first administration date of the most recent continuous administration period was used if there was a period of non-administration for more than 1 year. The time to onset of AEs for analysis was limited to 2 years (730 days).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The time to onset was calculated for each adverse event and the number of cases was counted for reports in which the date of onset of adverse events, the date of the start of administration, and the date of the end of administration were described as year/month/day or year/month [15]. The onset time was calculated as "(onset date of adverse event) -(administration start date) + 0.5" in principle [17]. If there was a period of non-administration for more than 1 year, the date of rst administration for the most recent continuous administration period was used.…”
Section: Statistical Analysesmentioning
confidence: 99%